57.0k views
6 votes
Write the following Arithmetic Sequence using a Recursive Formula: an = -7 + 3(n – 1)

a1 = 3, an = an-1 – 7
a1 = -7, an = an-1 + 3
a1 = -7, an = an+1 + 3
a1 = 3, an = an+1 – 7

User Dan Kanze
by
5.1k points

1 Answer

6 votes

9514 1404 393

Answer:

(b) a[1] = -7, a[n] = a[n-1] + 3

Explanation:

Comparing the given formula to the general form for the n-th term of an arithmetic sequence ...

an = a1 +d(n -1)

we see that the first term (a1) is -7, and the common difference (d) is +3.

The recursive version of the sequence definition is ...

a[1] = a1

a[n] = a[n-1] +d

So, the appropriate choice is ...

a[1] = -7, a[n] = a[n-1] +3

User Iyke
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.